Examining the association between pruritus and quality of life in patients with atopic dermatitis treated with crisaborole. (7th July 2019) - Ständer, S.; Yosipovitch, G.; Bushmakin, A.G.; Cappelleri, J.C.; Luger, T.; Tom, W.L.; Ports, W.C.; Zielinski, M.A.; Tallman, A.M.; Tan, H.; Gerber, R.A.
Abstract: Background: Pruritus is a leading cause of reduced health‐related quality of life (QoL) in atopic dermatitis (AD). Crisaborole ointment is a non‐steroidal phosphodiesterase 4 inhibitor for the treatment of mild‐to‐moderate AD. In identical Phase 3 studies (NCT02118766, NCT02118792), crisaborole reduced disease and pruritus severity versus vehicle. Objective: Quantify the relationship between pruritus and QoL using data from these studies. Methods: Patients aged ≥2 years were randomly assigned 2 : 1 to receive crisaborole:vehicle twice daily for 28 days. QoL was measured at baseline and day 29 using the Dermatology Life Quality Index (DLQI; patients aged ≥16 years), the Children's Dermatology Life Quality Index (CDLQI; patients aged 2–15 years) and the Dermatitis Family Impact (DFI; caregivers of patients aged 2–17 years). Pruritus was measured using the Severity of Pruritus Scale (SPS), a 4‐point scale from 0 ('no itching') to 3 ('bothersome itching/scratching that disturbs sleep'), and captured morning and evening via electronic diary. Data from crisaborole and vehicle arms were pooled for this analysis. A repeated‐measures longitudinal model was used to estimate relationships between pruritus (SPS) and QoL (DLQI, CDLQI and DFI in separate analyses). Results: One thousand five hundred and twenty two patients received crisaborole or vehicle. A linearity assumption for the relationship between SPS and DLQI ( n = 294), CDLQI ( n = 1200), and DFI ( n = 1293) was appropriate. For DLQI, SPS score of 0 was associated with 'no negative effect on patient QoL'; SPS score of 1 was associated with 'small effect on patient QoL'; SPS score of 2 was associated with 'moderate effect on patient QoL'; and SPS score of 3 was associated with 'very large effect on patient QoL'. The pattern of relationships between SPS and CDLQI and DFI was similar. Conclusions: The relationships between SPS and DLQI, CDLQI and DFI substantiate the significant link between pruritus and patient/caregiver QoL in AD.